Single Camera-Based Gait Analysis Using Pose Estimation for Ankle-Foot Orthosis Stiffness Adjustment on Individuals With Stroke - Masataka Yamamoto; Koji Shimatani; Daisuke Matsuura; Yusuke Murakami; Naoya Oeda; Hiroshi Takemura (IEEE Journal of Translational Engineering in Health and Medicine)
Introduction: Stroke is one of the most common causes of impaired gait. The use of an ankle-foot orthosis (AFO) is one of the recommended methods to improve gait function in stroke patients. Although the stiffness of the AFO is adjusted for each stroke patient, the effect of stiffness adjustment remains unclear due to the difficulty in measuring the gait parameters in a clinical setting. Objective: This study aimed to investigate the effect of adjusting the AFO stiffness based on the gait ability of stroke patients using a markerless gait analysis method. Methods: A total of 32 individuals with stroke were directed to walk under five conditions: no-AFO and AFO with four different levels of spring stiffness. These springs were used to resist the plantarflexion movements. Moreover, the best gait speed improvement condition (best condition) was determined from the five gait conditions for each participant and was compared with the other conditions, assuming a clinical setting. Spatiotemporal gait parameters such as the gait speed, cadence, step length, stance phase, and swing phase were measured from body keypoints in RGB images. Results and Conclusion: The experimental results showed that the gait speed, cadence, step length on both sides, and stance time on both sides were significantly improved in the best condition compared with the other conditions. This study demonstrated the usefulness of the markerless gait analysis method using a single RGB camera and the effectiveness of AFO stiffness adjustment based on the gait ability of the users.